Agriculture in Eastern Europe - Durand, E. Dana (Quarterly Journal of Economics, 1922)
I. Overcrowding of the land, 170. — Importance of agricultural problem of eastern Europe. Density of population. Large proportion of rural population; its high density. Low yields. Per capita grain production. II. Consequences as to standard of living and food supply, 174. — Predominantly vegetable diet. Small surplus after supplying wants of producer. Live stock. Prewar grain exports. Reduction of food output during war; continuation of similar causes after war. Widespread food shortage. The Russian famine. III. Prospects for recovery, 180. — Conditions favoring recovery. Importance of political conditions. Increased crops of 1921 except in Russia; exports of food; effect on currency exchange. Probably slower recovery of Russia. IV. Prospect for progress in peasant agriculture, 183. — Vicious circle of overcrowding, poverty, ignorance. Effects of overcrowding on agricultural methods. Shallow plowing. Unsatisfactory crop rotation. Scattered holdings — their explanation and consequences. Mir system. Beneficial effects of democracy. Rapid progress improbable. V. The large estates, 190. — Large-scale operation. Superior efficiency. Polish estates. Agrarian reform — division of estates. Direct gain to peasant overestimated. Measures already taken. Ultimate effects, especially on peasant psychology.